A prospective analysis of telomere length and pancreatic cancer in the alpha‐tocopherol beta‐carotene cancer (ATBC) prevention study. Issue 11 (14th June 2013) - Lynch, Shannon M.; Major, Jacqueline M.; Cawthon, Richard; Weinstein, Stephanie J.; Virtamo, Jarmo; Lan, Qing; Rothman, Nathaniel; Albanes, Demetrius; Stolzenberg‐Solomon, Rachael Z.
<x xml:space="preserve">Abstract</x> Smoking and diabetes, consistent risk factors for pancreatic cancer, are also factors that influence telomere length maintenance. To test whether telomere length is associated with pancreatic cancer risk, we conducted a nested case–control study in the Alpha‐Tocopherol, Beta‐Carotene Cancer Prevention (ATBC) Study cohort of male smokers, aged 50–69 years at baseline. Between 1992 and 2004, 193 incident cases of pancreatic adenocarcinoma occurred (mean follow‐up from blood draw: 6.3 years) among participants with whole blood samples available for telomere length assays. For these cases and 660 controls, we calculated odds ratios (OR) and 95% confidence intervals using unconditional logistic regression, adjusting for age, number of years smoked regularly, and history of diabetes mellitus. Telomere length was categorized into quartiles (shortest to longest) and analyzed as both a categorical and a continuous normal variable (reported per 0.2 unit increase in telomere length). All statistical tests were two‐sided. Longer telomere length was significantly associated with increased pancreatic cancer risk (continuous OR = 1.26 95% CI = 1.09–1.46; highest quartile compared to lowest, OR = 1.57, 95% CI = 1.01–2.43, p‐trend = 0.007). This association remained for subjects diagnosed within the first five years of blood draw (continuous OR = 1.46, 95% CI = 1.19–1.79 highest quartile OR = 2.92, 95% CI = 1.47–5.77, p‐trend = 0.002), but not those diagnosed greater than five years after blood draw (continuous OR = 1.03, 95% CI = 0.85–1.22; highest quartile OR = 1.04, 95% CI = 0.60–1.79). This is the first prospective study to suggest an association between longer blood leukocyte telomere length and increased pancreatic cancer risk.